(2E)-1-(4,4′′-Difluoro-5′-methoxy-1,1′:3′,1′′-terphenyl-4′-yl)-3-(2-fluorophenyl)prop-2-en-1-one - Fun, Hoong-Kun (International Union of Crystallography, 2012)
In the title compound, C(28)H(19)F(3)O(2), the central benzene ring forms dihedral angles of 48.69 (6), 60.93 (6) and 42.06 (6)° with the fluorobenzene rings. In the crystal, intermolecular C—H⋯O and C—H⋯F hydrogen bonds link the molecules, forming an undulating two-dimensional network parallel to the bc plane. C—H⋯π interactions further consolidate the crystal packing.